Bangunan Heritage Sebagai Materi Pembelajaran Daring Tematik - Putri, Tika Novis; Syahriyah, Dewi Rachmaniatus; Sancoko, Bagas Destio (Jurnal Pengabdian Tri Bhakti, 2020)
The Covid – 19 pandemic has been generated the biggest disruption of education teaching and learning methods at all levels of education, from kindergarten to tertiary institution. Distance learning solutions were developed as a quick response to support education continuity. At the early childhood educations, the teachers are expected to adjust quickly to create attractive and innovative learning materials to replace face-to face learning in school and to make it easier for parents who accompany her children at home. Based on those issues, and the contect of distance learning currently held by schools, this Community Services Program are carried out by designing learning material packages that can be used by the kindergarten teachers to teach thematic learning online. The theme developed in this program is expected to replace the study tour around Bandung activity which is regularly held by school every year, in the form of project based learning for kindergarten with tutorial video available. Partner involved in this community services program is Taman Firdaus Percikan Iman (TPFPI), in Ciwaruga, Parongpong, Bandung Barat. Those learning materials packages regarding the introduction of heritage building in Bandung City by through fine motor and cognitivie stimulation activities. Thus, hopefully the results of this community services program can be an alterative solution for distance learning models, not only in TPFPI but also in other kindergartens in Bandung City.